2008
DOI: 10.1038/sj.bjc.6604425
|View full text |Cite
|
Sign up to set email alerts
|

Sleep duration and the risk of prostate cancer: the Ohsaki Cohort Study

Abstract: In a prospective study of prostate cancer incidence (127 cases), among 22 320 Japanese men, sleep duration was associated with lower risk; the multivariate hazard ratio of men who slept X9 h per day compared with those who slept less was 0.48 (95% confidence interval: 0.29 -0.79, P for trend ¼ 0.02). Pinheiro et al, 2006). Melatonin, which is secreted mainly from the pineal gland and plays a role in sleep duration, is suggested as one of the candidates responsible for the association in breast cancer (Brzezin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
77
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(82 citation statements)
references
References 27 publications
3
77
2
Order By: Relevance
“…Finally, 12 articles fulfilling the inclusion criteria were included in the meta-analysis. Among these 12 articles, five studies reported breast cancer (Verkasalo et al, 2005;Pinheiro et al, 2006;Kakizaki et al, 2008b;Vogtmann et al, 2013;Wu et al, 2013), two studies on colorectal cancer (Jiao et al, 2013;Zhang et al, 2013), one each study on prostate cancer (Kakizaki et al, 2008a), endometrial cancer (Sturgeon et al, 2012), epithelial ovarian cancer (Weiderpass et al, 2012), thyroid cancer (Luo et al, 2013), and all type cancers (von Ruesten et al, 2012).…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 12 articles fulfilling the inclusion criteria were included in the meta-analysis. Among these 12 articles, five studies reported breast cancer (Verkasalo et al, 2005;Pinheiro et al, 2006;Kakizaki et al, 2008b;Vogtmann et al, 2013;Wu et al, 2013), two studies on colorectal cancer (Jiao et al, 2013;Zhang et al, 2013), one each study on prostate cancer (Kakizaki et al, 2008a), endometrial cancer (Sturgeon et al, 2012), epithelial ovarian cancer (Weiderpass et al, 2012), thyroid cancer (Luo et al, 2013), and all type cancers (von Ruesten et al, 2012).…”
Section: Search Resultsmentioning
confidence: 99%
“…The study samples ranged from 12, 222 to 142, 933, and the median of the follow-up durations is 11.3 years. Nine studies focused on the cancer of women, one only on men (Kakizaki et al, 2008a), one on men and women combined (von Ruesten et al, 2012), and one reporting men and women separately according to different cohorts (Zhang et al, 2013). Most of studies reported the sleep duration of 24 hours period, while four studies investigated typical night sleep duration (Sturgeon et al, 2012;Jiao et al, 2013;Luo et al, 2013;Vogtmann et al, 2013).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Dr. Sturgeon et al [4] now provide the sixth study on the issues concerned and report mixed results. Overall, with regard to how long one sleeps, first [4][5][6][7][8]-but not all [9]-epidemiological evidence could be viewed in line with increased cancer risks in those who sleep less than others [2].…”
Section: Introductionmentioning
confidence: 99%
“…See Table III for an example with calculations explained. Figure 5 graphs the relationship between sleep duration and breast cancer in Japan and Singapore [10,14], as well as prostate cancer in Japan [11].In order to test the hypothesis, that incident and reflected waves of horizontally polarized radiation cancel each other close to a metal structure and might add as standing waves further up from it, we measured the electric fields of FM-radio signals above beds with and without a metal spring mattress. A horizontal monopole antenna (0.5 metre) was connected to spectrum analyser (GW Instek, GSP 827, Taiwan).…”
mentioning
confidence: 99%
“…Despite increasing screening and lifestyle changes, there is no conclusive explanation for this rather sudden increase in breast cancer incidence after 1955, which was also noted for skin melanoma and some other cancers. In 2002, it was hypothesized that body-resonant broadcast radiation might act as a threat to the immune system of people who tended to sleep for years in resonance with an FM radio main transmitter [2] If a person sleeps on a metal spring mattress, reflected and standing waves could also explain the fact that the left side of the body in general is more prone to breast cancer [11][12][13][14] and melanoma [1] than the right side of the body. This can be explained by the fact that people tend to sleep for longer times on the right side than on the left side, so that the right side is closer to the field attenuating metal than the left side is [3].…”
mentioning
confidence: 99%